An evaluation of the Umbumbulu Agri-Hub as a model to support small-scale farmers. (June 2015) - Gilmore, Peter; Chasomeris, Mihalis
The purpose of this study was to critically evaluate the Umbumbulu Agri-Hub in eThekwini, KwaZulu-Natal as a successful model for supporting rural small-scale farmers. The Umbumbulu Agri-Hub, a Rural Agricultural Services and Marketing Hub, was implemented by the eThekwini Municipality on a pilot basis, for three years, with the intention of rolling it out to other parts of the municipality. Data were collected from 49 farmers, from five selected representatives from the hub, from the eThekwini and iLembe Municipalities and from the KwaZulu-Natal Department of Agriculture. The findings show extensive support for the agricultural extension services offered by the hub, and that the hub has had a positive impact on the farmers as a conduit through which extension services can be provided to small-scale farmers in the rural area of Umbumbulu.